Medial-lateral gait patterns in healthy adult walkers - Claff, D; Williams, M; Blakeborough, A; Stebbins, J (2013)
With over a decade of research into the causes and effects of footbridge lateral excitation, models have emerged to describe pedestrian motion and force patterns. Authors have suggested, however, that insufficient data are available for model comparison. Thus, the medial-lateral (M-L) ground force, centre of pressure (CoP) location, and centre of mass (CoM) location were collected for over 300 healthy adult male and female footsteps. The data were collected using two AMTI force plates (1000 Hz) and a Vicon motion capture system (100 Hz). Using MATLAB, the data were analysed: the subsequent qualitative and quantitative observations are the topic of this paper. Inter- and intra-subject trends were observed among force-time correlations, CoP and CoM paths, and force-CoP plots. Additionally, the M-L force data were also compared to the inverted pendulum model to assess the model's accuracy in predicting individual step behaviour. Conclusions are drawn that while walkers exhibit consistency in M-L force strategy over repeated footsteps, their steps do not tend to match the population mean. Furthermore, the inverted pendulum model proves poor in predicting either the population or the individual participants. This supports the theory that lateral pedestrian motion and forces should be modelled as stochastic processes. © The Society for Experimental Mechanics, Inc. 2013.